Pengaruh Model Pembelajaran Discovery Learning Berbasis Think Pair Share Terhadap Hasil Belajar Matematika ditinjau dari Penalaran Matematika Siswa Kelas VIII SMP Negeri 1 Sambi - Pamungkas, Anggoro Yugo, Dra. Nining Setyaningsih, M.Si (2017)
This study aimed to analyze and examine (1) effect of learning model Discovery Learning-based Think Pair Share the learning outcomes of mathematics, (2) the effect of the level of mathematical reasoning students' learning outcomes mathematics, and (3) the interaction model of learning Discovery Learning-based Think Pair Share and level mathematical reasoning students' mathematics learning outcomes. This type of research is quantitative research with quasi experiment. This study population is the entire class VIII SMP Negeri 1 Sambi 2016/2017. The sample in this study consisted of two classes with sampling techniques using random cluster sampling. Data collection techniques using methods of documentation, test and questionnaire. Data were analyzed using two-way analysis of variance technique with different cells. Research results with significance level of 5% is (1) there is an effect of learning model Discovery Learning-based Think Pair Share the results of students 'mathematics learning with FA = 4,832, (2) there was an effect of mathematical reasoning on the results of students' mathematics learning with FB = 8,988, and (3) there is no interaction between the learning model based Discovery learning Think Pair Share and mathematical reasoning students with FAB = 2,099.